Collaboratively reframing mental health for integration of HIV care in Ethiopia(†) - Wissow, Lawrence S. (Health Policy Plan, 2015)
Background Integrating mental health with general medical care can increase access to mental health services, but requires helping generalists acquire a range of unfamiliar knowledge and master potentially complex diagnostic and treatment processes. Method We describe a model for integrating complex specialty care with generalist/primary care, using as an illustration the integration of mental health into hospital-based HIV treatment services in Ethiopia. Generalists and specialists collaboratively developed mental health treatments to fit the knowledge, skills and resources of the generalists. The model recognizes commonalities between mental health and general medical care, focusing on practical interventions acceptable to patients. It was developed through a process of literature review, interviews, observing clinical practice, pilot trainings and expert consultation. Preliminary evaluation results were obtained by debriefing generalist trainees after their return to their clinical sites. Results In planning interviews, generalists reported discomfort making mental health diagnoses but recognition of symptom groups including low mood, anxiety, thought problems, poor child behaviour, seizures and substance use. Diagnostic and treatment algorithms were developed for these groups and tailored to the setting by including possible medical causes and burdens of living with HIV. First-line treatment included modalities familiar to generalists: empathetic patient–provider interactions, psychoeducation, cognitive reframing, referral to community supports and elements of symptom-specific evidence-informed counselling. Training introduced basic skills, with evolving expertise supported by job aides and ongoing support from mental health nurses cross-trained in HIV testing. Feedback from trainees suggested the programme fit well with generalists’ settings and clinical goals. Conclusions An integration model based on collaboratively developing processes that fit the generalist setting shows promise as a method for incorporating complex, multi-faceted interventions into general medical settings. Formal evaluations will be needed to compare the quality of care provided with more traditional approaches and to determine the resources required to sustain quality over time.